Effect of matrix and hybrid reinforcement on fibre metal laminates under low–velocity impact loading. (15th May 2022) - Hussain, M.; Imad, A.; Nawab, Y.; Saouab, A.; Herbelot, C.; Kanit, T.
Abstract: This study aims to investigate the effect of matrix and hybrid reinforcement on Low–Velocity Impact LVI behaviour of Fibre Metal Laminates FMLs. The matrix was epoxy and Poly–Vinyl Butyral PVB, while the reinforcement was produced by sandwiching 3D–woven jute core with plain–woven skin. The plain–woven fabric was made with jute, aramid and carbon fibres. A drop weight impact test was performed for the evaluation of LVI performance. The behaviour of different FMLs was determined by comparing the pattern of curves, cross–section of damaged samples, x–ray computed tomography and crack progression phenomenon. The epoxy–based FMLs showed poor LVI response and suffered perforation due to its brittleness. The PVB–based FMLs showed higher impact resistance due to high toughness and plasticity, and had a higher impact force, lower damage, and more residual deflection. Even PVB based 100% jute reinforced FMLs performed well than hybrid reinforced FMLs made with epoxy. The tomography analysis showed that the PVB had better characteristics to be used with hybrid reinforcement due to high toughness. Among the hybrid reinforcements, the aramid/3D–jute reinforcement offered high resistance to deformation as compared to carbon/3D jute reinforcement. The FMLs made with PVB and aramid/3D–jute reinforcement showed overall superior LVI performance.